1995
DOI: 10.1212/wnl.45.12_suppl_8.s63
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical allodynia in postherpetic neuralgia

Abstract: In 12 zoster patients who had developed postherpetic neuralgia with dynamic mechanical allodynia and in six zoster patients who had recovered without pain, the functional role of nociceptive C-fibers in allodynia was assessed by quantifying axon reflex reactions induced by histamine iontophoresis within allodynic regions and in their contralateral sites. In patients with postherpetic neuralgia, histamine responses were reduced or abolished within allodynic areas, indicating degeneration of nociceptive C-fibers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 5 publications
0
24
0
1
Order By: Relevance
“…The neurophysiological findings in this patient receive support from supraorbital biopsy studies, indicating that this neuropathy predominantly affects the Aβ afferents and spares C fibres. This is an unexpected finding because these patients typically complain of constant burning pain, a symptom that in limb pains is usually attributed to C-fibre deafferentation [42].…”
Section: Involvement Of the Gasserian Ganglionmentioning
confidence: 87%
“…The neurophysiological findings in this patient receive support from supraorbital biopsy studies, indicating that this neuropathy predominantly affects the Aβ afferents and spares C fibres. This is an unexpected finding because these patients typically complain of constant burning pain, a symptom that in limb pains is usually attributed to C-fibre deafferentation [42].…”
Section: Involvement Of the Gasserian Ganglionmentioning
confidence: 87%
“…29,30 Furthermore, functional studies investigating C-fiber axon reflex have demonstrated impaired or abolished chemically evoked antidromic vasodilatation in skin regions with intense dynamic allodynia, indicating a significant loss of cutaneous C-fiber afferents. 31,32 There is evidence that all sensory fiber types are affected in PHN, with constant pain possibly being associated with damage to nociceptive afferents and paroxysmal pain related to changes in A␤ fibers. 33 Quantitative thermal sensory testing showed greatly increased heat pain thresholds in the affected dermatome of some chronic PHN patients.…”
Section: Postherpetic Neuralgiamentioning
confidence: 99%
“…The causes of postherpetic neuralgia are complex and thought to involve not only neural damage in the peripheral but also in the central nervous system [25]. The vulnerability-diathesis-stress model [3••] illustrates the role of stress in the development of postherpetic neuralgia (Fig.…”
Section: The Influence Of Stress On the Development Of Postherpetic Nmentioning
confidence: 99%